Ochrona zdrowia jako element polityki publicznej - Barańska, Marzena (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
Public health is strictly related to health policy, since political decisions determine the selection of priorities and the distribution of assets. Health, perceived in this way, is protected by global activities, and not only by a given country or region. Health is a significant element among the tasks handled by public authorities. A consequence of these activities is ensuring medical care by means of developing the right apparatus and mechanisms of solutions allowing for common access to treatments offered.